The Development of Mathematical Problems in the Context of the Bangka Belitung Traditional House to Train Mathematical Communication Skills - Selvy Zananti; Risnina Wafiqoh; Rajab Vebrian (Department of Mathematics, Universitas Negeri Padang (UNP), 2023)
The problem that is currently happening is that students' mathematical communication skills are still low. Based on the review where students were given questions, students were not able to make a mathematical model as a solution to solve the problem. So, this research was conducted to find out the characteristics of valid and practical mathematical questions using the context of the Bangka Belitung traditional house. The research and development model used in this study is the Borg and Gall development model. The subjects in this study were students of class VII at one of the Pangkalpinang State Middle Schools, with 40 students, consisting of 9 students in class VII B and 31 students in class VII C. Data collection techniques were conducted by interviews and questionnaires. The data analysis techniques used are descriptive quantitative and descriptive qualitative. This study develops questions with the characteristics that have been developed according to mathematical communication indicators, using the context of the Bangka Belitung traditional house, and planes.